Development of a mariner-Based Transposon for Use in Sorangium cellulosum - Julien, Bryan (American Society for Microbiology, 2003)
In order to generate marked insertions in the myxobacterium Sorangium cellulosum, a transposon based on the eukaryotic mariner transposon was developed. The transposition frequency was increased with the use of a mutated tnp gene. The transposon randomly inserts into the chromosome, as demonstrated by targeted mutagenesis of the epoK gene.